Species Diversity and Distribution of Non-volant Small Mammal between Restoration, Boundary, Disturbed and Undisturbed Area in Cameron Highlands, Malaysia - Nur Syakirah Baharudin; Marina Mohd. Top@Mohd. Tah; Syaizwan Zahmir Zulkifli; Nurul Izza Ab Ghani; Hafidzi Mohd Noor; Nabilah Hamidah Sabar@Sabal (Tropical Life Sciences Research, 2023)
Deforestation in Cameron Highlands, Malaysia has increased significantly in the past few years to accommodate the growing population of Cameron Highlands. This led to a rapid urbanisation in Cameron Highlands which increased anthropogenic activities, causing degradation of the natural environment. Such environmental changes highlight the necessity of wildlife and resource inventories of available forested areas to improve existing conservation and management plans, especially for threatened taxa such as the non-volant small mammals. However, very few studies are known to focus on the effect of deforestation on non-volant small mammals, especially in the adjacent forest. This survey aimed to document non-volant small mammals from four habitat types (restoration areas, boundary, disturbed and undisturbed areas) of Terla A and Bertam, and undisturbed forest of Bukit Bujang Forest Reserve, Cameron Highlands, Malaysia. Samplings were conducted in two phases between August 2020 to January 2021. A total of 80 live traps were deployed along the transect lines in all three study sites, and 10 camera traps were set randomly in each forested area. Results demonstrated that species diversity (H’) is higher at Terla A Forest Reserve compared to Bertam and Bukit Bujang Forest Reserve. In contrast, species diversity in the boundary area (S = 8, H’ = 2.025) and disturbed forest area (S = 8, H’ = 1.992) had similar number of species (S) compared to others study habitat; restoration area had the lowest species diversity (S = 3, H’ = 0.950). Berylmys bowersi was the most captured species from trappings and Lariscus insignis was the most frequently recorded species from camera trappings for all study sites. The results of the survey provided new information on non-volant small mammals in Cameron Highlands for future research, conservation, and management.